2001
DOI: 10.1016/s0022-5347(05)65984-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonbladder Related Symptoms in Patients With Interstitial Cystitis

Abstract: Patients with interstitial cystitis had increased scores for 9 reference symptoms but did not indiscriminately report high scores for generalized complaints. This result suggests that in some cases of interstitial cystitis the pathophysiology may affect other organ systems besides the bladder. Alternatively, some of these symptoms may result from changes in sleep pattern or other factors associated with interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Although reports of extrapelvic symptoms in IC/BPS cases 1,2 and an association with other functional pain syndromes such as IBS and fibromyalgia are not new, 35 to our knowledge the possibility that somatization disorder presents in a classic PSPS pattern has not previously been considered in the UCPPS literature. We thought that this possibility should be further investigated in a subset of patients with complaints of numerous extrapelvic symptoms.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although reports of extrapelvic symptoms in IC/BPS cases 1,2 and an association with other functional pain syndromes such as IBS and fibromyalgia are not new, 35 to our knowledge the possibility that somatization disorder presents in a classic PSPS pattern has not previously been considered in the UCPPS literature. We thought that this possibility should be further investigated in a subset of patients with complaints of numerous extrapelvic symptoms.…”
Section: Discussionmentioning
confidence: 93%
“…This may explain why extrapelvic symptoms are more prevalent among female patients with IC/BPS in previous studies. 1,2 Patients with IC/BPS may be characterized into 3 subgroups, including those with 1) bladder symptoms only, 2) pelvic symptoms and 3) multiple symptoms of other organ systems, eg fibromyalgia and IBS. 21 Although we did not specifically test this hypothesis in this study, our results raise the possibility that in a subset of patients with UCPPS, eg those with multiple symptoms of other organ systems, somatization disorder may be one of the common processes that help explain the association between UCPPS and other functional syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an association between IC/BPS, CP/CPPS and chronic overlapping pain syndromes (COPC) such as irritable bowel syndrome, fibromyalgia, and chronic fatigue syndrome 13 with some studies reporting systemic (e.g., poly-symptomatic, poly-syndromic) symptom presentation. 4, 5 It has been hypothesized that patients with localized pelvic pain might represent a different phenotype than those with more widespread systemic pain. 6, 7 However to date, very few studies have characterized the location of body pain among men and women with IC/BPS or CP/CPPS.…”
mentioning
confidence: 99%
“…These extra-pelvic symptoms may be painful (e.g., abdominal pain) or non-painful (e.g., numbness, dizziness, palpitation). 1, 2 We have previously shown that about one out of four UCPPS patients reported numerous somatic symptoms in a classic “poly-symptomatic, poly-syndromic” (PSPS) pattern of presentation. 3 The defining features of PSPS are that patients complain of numerous symptoms that are also widely distributed across multiple organ systems.…”
Section: Introductionmentioning
confidence: 99%